Quantitative measurement of intracellular metabolic changes in Clostridium autoethanogenum using liquid chromatography isotope dilution mass spectrometry - Safo, Laudina (2018)
Clostridium autoethanogenum is an important organism for biofuel production. Other ’omics’ approaches have been used to understand the mode of operation of the organism but metabolomics gives information on the cellular activities in the cell. Metabolomics combined with other ‘omics’ data can provide a deeper understanding for pathway interpretation. This project sets out to develop an analytical method that is suitable for analysis of highly charged polar compounds found in C. autoethanogenum metabolic pathways. Also investigate suitable isotope labelled internal standards to improve matrix effects to the metabolites as a result of the biological matrix. A high-throughput hydrophilic interaction liquid chromatography isotope dilution mass spectrometry (HILIC-IDMS) was developed and validated using high resolution hybrid orbital trap MS for both targeted and untargeted metabolomics analysis of intracellular metabolic pathways of Clostridium autoethanogenum. Extraction of intracellular metabolites from C. autoethanogenum was achieved using a specifically developed sample preparation protocol using freeze thaw cycles (freeze in liquid nitrogen and thaw on ice repeated 3x). A total of 133 metabolites were monitored and validated. Limits of detection (LODs) ranged from 0.001 µM to 5 µM reported for compounds such as NADPH and NADH. Limits of quantification (LOQs) for all metabolites ranged from 0.001 µM to 10 µM for metabolites such as glucose-6-phosphate and glyceraldehyde-3 phosphate. Precision and accuracy were evaluated for all metabolites and found to be within the acceptable limits of ±15 % with few exceptions for some nucleotides and organic acids. Stable isotopically labelled internal standards were generated from C. pasteurianum cells that provided coverage for about 100 metabolites. This enabled absolute intracellular concentrations to be obtained in combination with the estimated cell volume of C. autoethanogenum that was obtained from microscopy and flow cytometry measurements. The developed HILIC-IDMS method was applied to various solvent production optimisation experiments conducted using C. autoethanogenum and the main findings are reported below. In chapter 4, the HILIC-IDMS method was applied to C. autoethanogenum in an experiment where the pH of the media was reduced to improve ethanol and solvent production. The metabolomics studies of this experiment gave intracellular concentrations that differentiated the acidogenic phase from the solventogenic phase. A total of 86 metabolites were quantified in this experiment. Intermediates in the tricarboxylic acid (TCA) cycle were the most affected during the acidogenic/solventogenic transition. Metabolites concentrations were used for metabolic pathways analysis to understand the pathways affected during the pH shift. The pathway analysis also confirmed the TCA cycle was the most affected pathway during the acidogenic/solventogenic transition. In chapter 5, The HILIC-IDMS method was applied to a gas shift experiment to optimise ethanol and solvent production. Gas shift is another approach that can be used to optimise solvent production in similar as the pH shift experiment. The use of gas shift to induce solventogenic phase can be difficult as C. autoethanogenum has little tolerance for high levels of CO hence the increase in gas (CO) flow rate has to be done in a gradual fashion. Equally, TCA intermediates were observed to be the most affected as observed in the pH shift experiment. In chapter 6, the method was applied to a study where pantothenate and phosphate concentrations in the growth media of C. autoethanogenum were reduced to increase ethanol production. Pantothenate is the precursor for coenzyme A (CoA) production and metabolomics study confirmed a decrease in CoA concentration when pantothenate concentration was reduced. Metabolomics also showed decrease in concentration of metabolites directly linked to CoA synthesis such as L- Aspartate. Metabolic pathway analysis also confirmed the pantothenate and CoA biosynthesis and its associated pathways were the most affected pathways during the pantothenate-limiting phase. Both targeted and untargeted metabolomics analysis were performed on these nutrient-limiting experiments and there were clear differences between the two different conditions before and after nutrient limitation. Supervised multivariate data analysis using OPLS-DA was used to compare higher pantothenate and low pantothenate concentration and there were clear separation and clustering between the two conditions. Cross validation obtained for R2Y and Q2 were 0.993 and 0.941 respectively. OPLS-DA plots for phosphate limitation also showed clustering and separation between the high phosphate concentration and reduced phosphate concentration with R2Y and Q2 0.981and 0.837 respectively. In conclusion, a novel high-throughput HILIC-IDMS method was developed and validated for analysis of different classes of polar compounds in bacteria. The method has the potential to be applied in other biological matrices for coverage of diverse range of polar compounds.